Napâttuit: Wood use by Labrador Inuit and its impact on the forest landscape - Lemus-Lauzon, Isabel; Bhiry, Najat; Woollett, James (Études/Inuit/Studies, 2012)
AbstractIn Nunatsiavut, recent studies have shown that major changes to forest tundra ecosystems have occurred over the past two centuries, including a shift in the abundance and range of tree/shrub species. Although this trend could be due to the highly variable climate of this period, we should also consider anthropogenic factors, such as wood harvesting, when conducting ecological studies of forest dynamics. Based on a literature review, interviews, and field observations, this article documents the interactions between residents of Nain (Nunatsiavut) and the forest landscape since the late 18th century. Nain is one of the few Inuit communities south of the tree line, and its inhabitants seem to have had an ambivalent and changing relationship with their forest landscape. Thus, though probably perceived initially as potentially dangerous, the forest has gradually been integrated into land use patterns and helped shape some aspects of Labrador Inuit culture. For Nain’s inhabitants, wood use has been continuous but not homogenous over time. Patterns of use and harvesting have changed with the socio-economic setting and have left their traces on the region’s forest stands, as is evident from the abundance of cut stumps and the scarcity of naturally dead trees.